Predicting the recidivism of mentally disordered firesetters - Rice, M. E. (Journal of interpersonal violence, 1996)
The psychiatric literature has asserted that arsonists are a particularly dangerous group of mentally disordered offenders with a high likelihood of setting further fires, yet the scant empirical data do not support that contention. We examined the postrelease firesetting, violent, and nonviolent recidivism of 208 male firesetters who had been admitted to a maximum security psychiatric hospital. In an average period of 7.8 years at risk, 16% set another fire, 31% committed a violent offense, 57% committed a nonviolent offense, and 66% exhibited some form of recidivism. In general, personal characteristics that predicted firesetting recidivism were quite different from those that predicted nonviolent outcome and very different from those that predicted violent recidivism